Oxytocin receptor gene polymorphism - Wong, Rosa S; Chan, Yannis W. K; Tung, Keith T. S (Current psychology (New Brunswick, N.J.), 2024)
Oxytocin receptor gene polymorphism (OXTR rs53576) is associated with human social cognition and behavior. However, results on the contribution of OXTR rs53576 to individual differences in depressive symptoms have been inconsistent. This meta-analysis examined the association between OXTR rs53576 and depressive symptoms and under what conditions this association might hold true. A systematic search of PubMed, PsycInfo, and Web of Science was performed for English articles describing human-based studies from the inception of the databases to February 2023, as well as a manual search of the reference lists of the included articles. The search terms included OXTR rs53576, depressive symptoms, and their synonyms. Standardized mean differences in depressive symptoms between individuals classified by OXTR rs53576 genotypes were evaluated, and random-effects meta-analyses were performed. A total of 10 studies including 2972 subjects from six countries were pooled. Results provided no evidence of an association between OXTR rs53576 and depressive symptoms. The between-study differences in I2 statistics by ethnicity, disease history, and age group suggested the presence of moderating variables. However, the number of eligible studies was small with considerable heterogeneity. Findings underscore the importance of homogeneous sampling for research on depression genetics to affirm the association between OXTR rs35376 and depressive symptoms.